2022
DOI: 10.1038/s41598-022-05840-5
|View full text |Cite
|
Sign up to set email alerts
|

Young children’s screen time during the first COVID-19 lockdown in 12 countries

Abstract: Older children with online schooling requirements, unsurprisingly, were reported to have increased screen time during the first COVID-19 lockdown in many countries. Here, we ask whether younger children with no similar online schooling requirements also had increased screen time during lockdown. We examined children’s screen time during the first COVID-19 lockdown in a large cohort (n = 2209) of 8-to-36-month-olds sampled from 15 labs across 12 countries. Caregivers reported that toddlers with no online school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 56 publications
9
67
1
5
Order By: Relevance
“…Higher earnings were associated with lower screen time use in all modalities except video chat [ 31 ]. According to Bergmann et al [ 32 ] parents reported that young children not required to be in school were exposed to more screen time during lockdown than before. While this was exacerbated in countries with longer lockdowns, there was no evidence that increased screen time during lockdown was associated with sociodemographic variables, such as child age and socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Higher earnings were associated with lower screen time use in all modalities except video chat [ 31 ]. According to Bergmann et al [ 32 ] parents reported that young children not required to be in school were exposed to more screen time during lockdown than before. While this was exacerbated in countries with longer lockdowns, there was no evidence that increased screen time during lockdown was associated with sociodemographic variables, such as child age and socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the COVID-19 pandemic on increased screen time for all ages [ 61 ] is troubling given that screen time has been associated with obesity [ 62 ] and is a risk factor for severe obesity in children under 5 [ 63 ]. Children ages 3–7 across six countries reported increased screen time [ 64 ] and even children as young as 8–36 months are acquiring more screen time than before COVID-19 [ 65 ]. Future research should explore what providers know about why screen-time limits are recommended and to help develop training and tools to facilitate conversations between providers and parents about the importance of limiting screen time.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pandemic drastically reduced the possibility for outdoor activities throughout the globe, it is unsurprising that screen media exposure had increased dramatically among 3-17 year olds in (for a review, see Bergmann et al, 2022) and toddlers (Bergmann et al, 2022). In the United States, both total screen media exposure and problematic media use (de ned as a dependence that interferes with a child's usual functioning) increased among 2-11 year-olds, compared to pre-pandemic levels (Eales et al, 2021).…”
Section: Children Screen Times During the Pandemicmentioning
confidence: 99%